Application of dna techniques for the identification of two entomopathogenic nematode genera Steinernema and Heterorhabditis from Vietnam - Chau, Nguyen Ngoc; Long, Phan Ke (Academia Journal of Biology, 2014)
Entomopathogenic nematodes (epn), e.g. Steinernema Travassos, 1927 and Heterorhabditis Poinar, 1975 belong to one of the most important groups among biological agents. Their morphological identification to species level is very difficult. Since they are often homomorphic in the adult stage of the first generation, but they are strongly polymorphic and variable among different generations that are usually occurred even in the same species. Therefore, the molecular techniques have become useful tools for the identification and taxonomy of these nematodes. The DNA techniques such as polymerise chain reaction (PCR), restriction fragment length polymorphism (RFLP) and sequencing have been employed for the molecular characterization of entomopathogenic nematode isolates collected from Vietnam. Based on the morphological diagnoses, morphometrics and genetic analyses of 18S-rDNA of collected isolates from Vietnam were revealed 7 species of two genera Steinernema and Heterorhabditis so far. Of these, four species viz. Steinernema tami Pham et al., 2000, S. sangi Phan et al., 2001, S. loci Phan et al., 2001, and S. thanhi Phan et al., 2001 were described as new species for science. The results of the rDNA digestion with seventeen endoenzymes, e.g. Alu I, Mva I, Dde I, EcoR I, Hae III, Cfo I, Hind III, Hinf I, Msp I, Kpn I, Pst, Pvu II, Rsa I, Sal I, Nde II, Bsiz I and Xba I RFLP shown a significant difference in RFLP pattern between three isolates S-TK10, S-TG10, S-TX1 and that of S. Kraussei (Steiner, 1923) Travassos, 1927. Apparently, the complete differences which were occurred in six RFLP patterns digested by seven enzymes Alu I, Dde I, Cfo I, Hinf I, Msp I, Rsa I, Nde II. were not only by the band number but are also by the size (bp) of the DNA fragment lengths, inspite of five other enzymes were not digested any more. These might be documented the genetic similarly within the S. kraussei group. Along with some morphological characters and morphometrics, these genetic characterizations were strongly support to reveal three new species of three correspondent isolates. Based on the sequencing of 18S according ITS (Internal Transcribed Spacer) of DNA ribosome, the paper gives also the phylogenic tree that shown the related relationship and degree of genetic distance of species among each genus of Steinernema and Heterorhabditis and that were also significantly distinguished to Meloidogyne chitwoodi Golden, O’ Bannon, Santo & Finley, 1980.